Osteochondritis Dissecans of Smaller Joints: The Elbow. (October 2021) - Bruns, Juergen; Werner, Mathias; Habermann, Christian R.
This review presents the current understanding of the etiology, pathogenesis, and how to diagnose and treat osteochondritis dissecans (OCD) at the elbow joint followed by an analysis of particular characteristics and outcomes of the treatment. OCD is seen in patients with open growth plates (juvenile OCD [JOCD] and in adults [AOCD] with closed growth plates [adult OCD). The etiology at smaller joints remains as unclear as for the knee. Mechanical factors (throwing activities [capitulum] seem to play an important role. Clinical symptoms are unspecific. Thus, imaging techniques are most important for the diagnosis. In low-grade and stable lesions, treatment involves rest and different degrees of immobilization until healing. When surgery is necessary, the procedure depends on the OCD stage and on the state of the cartilage. With intact cartilage, retrograde procedures are favorable while with damaged cartilage, several techniques are used. Techniques such as drilling and microfracturing produce a reparative cartilage while other techniques reconstruct the defect with osteochondral grafts or cell-based procedures such as chondrocyte implantation. There is a tendency toward better results when reconstructive procedures for both the bone and cartilage are used. In addition, comorbidities at the joint have to be treated. Severe grades of osteoarthritis are rare.